Pengembangan Media Pembelajaran Berbasis Android Melalui Flip Pdf Pada Materi Mengolah Kue Traditional Indonesia Program Keahlian Kuliner SMKN 8 Surabaya - Icha Mayrani Purwanti; Niken Purwidiani; Lucia Tri Pangesthi; Sri Handajani (Jurnal Bintang Pendidikan Indonesia, 2024)
This study aims to determine: the results of the development of Android-based learning media through Flip PDF Professional on the material of Traditional Indonesian Cake Processing in class XI; the feasibility of Android-based teaching materials through Flip PDF Professional; the feasibility of Android-based learning media through Flip PDF Professional; and user responses to Android-based learning through Flip PDF Professional on the material of Traditional Indonesian Cake Processing. The research method used is development research with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. This research was only carried out up to the third stage, namely development, due to limited time and funds. Validation of the Android-based Flip PDF Professional involved one material expert and two media experts. Data collection was done through a questionnaire that included material validation, media, and Flip PDF user responses. The data analysis technique was quantitatively descriptive. The results showed: The results of the development of Flip PDF Professional are in the form of online links that include Traditional Indonesian Cake Processing material in the form of Flip PDF Professional; the feasibility of Traditional Indonesian Cake Processing material in the form of Flip PDF Professional is rated very feasible with an average of 81%; the feasibility of Traditional Indonesian Cake Processing media in the form of Flip PDF Professional is rated feasible with an average score of 74%; and user response, namely grade XI students of SMKN 8 Surabaya (majoring in culinary expertise) obtained an average score of 92% with very good interpretation. This shows that the development of Android-based multimedia through Flip PDF on Indonesian Traditional Cake Processing material can be used for learning traditional cake material.